2000
DOI: 10.1055/s-0037-1614124
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Antibodies Induced by Human Factor VIII in a Murine Knockout Model of Hemophilia A

Abstract: SummaryTo investigate the usefulness of factor VIII (FVIII) knockout mice as an animal model of hemophilia A, we characterized the antibody response in FVIII knockout mice to recombinant human FVIII, administered intravenously or subcutaneously with or without adjuvant, and compared results to those in normal mice. Anti-factor VIII antibodies were detected after both intravenous and subcutaneous administration, with the highest titers after subcutaneous administration plus adjuvant. Depending on the administra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
78
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 76 publications
(86 citation statements)
references
References 20 publications
(24 reference statements)
8
78
0
Order By: Relevance
“…The subcutaneous route of administration was investigated mainly to amplify the immune response. Further, Reipert et al (30) have reported that the IgG subtype levels were identical after subcutaneous and intravenous administration in hemophilia A mice, suggesting an identical mechanism of immune response for subcutaneous and intravenous routes. Blood samples were obtained in acid citrate dextrose buffer at various time points up to 6 weeks by cardiac puncture.…”
Section: Immune Responsementioning
confidence: 98%
“…The subcutaneous route of administration was investigated mainly to amplify the immune response. Further, Reipert et al (30) have reported that the IgG subtype levels were identical after subcutaneous and intravenous administration in hemophilia A mice, suggesting an identical mechanism of immune response for subcutaneous and intravenous routes. Blood samples were obtained in acid citrate dextrose buffer at various time points up to 6 weeks by cardiac puncture.…”
Section: Immune Responsementioning
confidence: 98%
“…Hemophilia A mice mount an IgG-based immune response similar to that of patients with hemophilia A (43). Immunizations were administered subcutaneously, and it has been shown that inhibitory titers to FVIII generated via this route are comparable to those following i.v.…”
Section: Immunogenicity Studiesmentioning
confidence: 99%
“…Anti-FVIII and anti-OVA IgG titers were determined by enzyme-linked immunosorbent assay as previously described. 47,48 Briefly, the solid phase of MaxiSorp flat-bottom 96-well plates (Nalge Nunc International, Rochester, NY) were coated with rhFVIII (0.2 ”g in 200 ”l/well) or OVA (0.4 ”g in 200 ”l/well) and then incubated with serial dilutions of mouse serum. The bound anti-FVIII or anti-OVA antibodies were detected by probing with an AP-conjugated goat anti-mouse IgG (Southern Biotech, Birmingham, AL) and developed using phosphatase substrate (Sigma-Aldrich).…”
Section: Suppression Of Fviii Inhibitors By Apoptotic Cellsmentioning
confidence: 99%